Hands-on blockchain with hyperledger : building decentralized applications with hyperledger fabric and composer /: building decentralized applications with hyperledger fabric and composer. (2018) - Baset, Salman; Desrosiers, Luc; Gaur, Nitin; Novotný, Petr; O'Dowd, Anthony; Ramakrishna, Venkatraman
No abstract available